Розв’язування системи рівнянь Нав’є-Стокса для оцінки динамічної рівноваги системи "галактика – космічний простір Всесвіту" - Онищук, Василь Варфоломійович (НТУ "ХПІ", 2017)
На основі аналітичного розв’язування замкненої системи рівнянь Нав’є-Стокса виконана оцінка морфологічного стану галактики Всесвіту при динамічній рівновазі системи "галактика – космічний простір Всесвіту". За отриманими розрахунковими формулами оцінено динамічну стійкість Всесвіту. Отримані результати розрахунків характеристик галактики дають можливість стверджувати про наявності в її центрі стійкого ядра у вигляді "чорної діри". Ядро галактики являє собою нейтральну зону у вигляді мезовира, який обертається проти годинникової стрілки і, таким чином, підтримує у поперечному вимірі динамічну рівновагу системи "галактика – космічний простір Всесвіту".

On the basis of analytical solving of a closed system of Navier-Stokes equations, an estimation of the morphological state of the universe's galaxy was performed at the dynamic equilibrium of the "galaxy-space universe" system. Based on the calculated formulas, the dynamic stability of the universe is estimated. The obtained results of calculations of the characteristics of the galaxy make it possible to assert the presence of a stable core in the form of a "black hole" in its center. The nucleus of the galaxy is a neutral zone in the form of a mesovirus, which rotates counter clockwise and thus supports in the transverse dimension the dynamic equilibrium of the system "galaxy – cosmic ray of the universe". Solving the closed Navier-Stokes equations and an example of calculating the main characteristics of the galaxy testify to the possibility of obtaining additional data on its morphological state. From the results of the study it is evident that changes in the characteristics of the galaxy are quite negligible, for example, the change in the radius of the galaxy is 9.44 10 – 28 %.
Solving the Navier-Stokes equations for estimating the dynamic equilibrium of the "galaxy-space universe" system
Keywords: пристінна зона; оператор Гамільтона; оператор Лапласа; системи рівнянь; система додаткових рівнянь; wall zone; dynamical system